Strength of edge column-slab connections of post-tensioned concrete flat plates. - Sharifi, Haki. (University of Ottawa (Canada), 1998)
The strength and behavior of edge column-slab connections of two way unbonded post-tensioned flat slab under uniformly distributed load were investigated. A square flat slab, two bays in each direction was constructed. The span of each bay was 3.2 m (10.5 ft) and the slab 89 mm (3.5 in) thick. Initially the slab behaved elastically and no residual deflections were observed upon releasing the load up to 5.8 kN/m$\sp2$ (0.85 psi). Punching shear failure happened at a load of 23.6 kN/m$\sp2$ at the edge column-slab connection #2. The failed connection(s) were repaired and shored, tendons re-tensioned and the slab reloaded to fail the next connection. To investigate the behaviour of corner column-slab connections all edge and the interior connections were shored. The measured moments and axial forces transferred to edge and corner columns were compared with those calculated by the Direct Design Method and Equivalent Frame Analysis. The shear strength obtained from the analysis of the experimental work was compared with previous research work, ACI 318-95 and CSA A23.3-94 concrete design codes and the 1995 Gardner proposed equation. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.